STRATEGY FOR DEVELOPMENT OF RASBORA GALAXY (DANIO MARGARIATUS) ORNAMENTAL FISH CULTIVATION BUSINESS AT MINA MAKMUR FARM BOJONGSARI DISTRICT, PURBALINGGA REGENCY OF CENTRAL JAVA PROVINCE - Krisnafi, Yaser; Wartini, Sri; Nugraha, Jefri Putri; Agustina, Yuli (PT. Hafasy Dwi Nawasena, 2024)
Ornamental fish cultivation is a business in the fisheries sector that is quite promising to develop. Market potential and high demand for ornamental fish, especially freshwater ornamental fish, further expand opportunities for developing ornamental fish cultivation. One of the regions with the largest ornamental fish production is Purbalingga Regency.One of the ornamental fish cultivated in Purbalingga Regency is the Rasbora Galaxy fish (Danio Margariatus). As an effort to develop the business of cultivating rasbora galaxy ornamental fish, an approach is needed to formulate the right strategy. One way or approach that can be taken to formulate an appropriate and effective business development strategy is through a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. The aim of this research is to determine the technical aspects of cultivating Rasbora Galaxy ornamental fish in Bojongsari District, Purbalingga Regency and identify factors, both internal and external that influence the development of the Rasbora Galaxy ornamental fish business, as well as determining priority business development strategies for the business using analysis. SWOT.The analysis method consists of analyzing internal factors with Internal Factor Evaluation (IFE), and analyzing external factors with External Factor Evaluation (EFE). The results of the IFE analysis obtained a value of0.53and EFE obtained a result of 0.89. The results of the SWOT analysis for this business are in quadrant 1, so the strategy applied is the SO (Strength-Opportunities) strategy. SO strategy is a strategy that utilizes internal strengths to capture existing opportunities